ANALISIS PENGARUH SANITASI LINGKUNGAN, PENGETAHUAN IBU DAN EKONOMI KELUARGA PADA STATUS GIZI BALITA DI DESA LUBUK SAKAT KABUPATEN KAMPAR - Kurniawan Kurniawan; Dedi Afandi; Agrina Agrina (Program Pascasarjana Universitas Riau, 2018)
The purpose of this study was to analyze the effect of environmental sanitation on toddlers nutritional status in Lubuk Sakat Village, Kampar Regency, analyze the influence of mothers knowledge levels on toddlers nutritional status in Lubuk Sakat Village Kampar Regency, and analyze the influence of family economic levels on toddlers nutritional status in Lubuk Sakat Village Kampar Regency. The research is located in the village of Lubuk Sakat in the working area of the Perhentian Raja Community Health Center in Kampar Regency from December 2018 to March 2019. The research approach used a quantitative approach that was analyzed descriptively analytically with a cross sectional design. The results showed that good environmental sanitation with good nutritional status for toddlers was 879.71%, while for poor environmental sanitation towards malnutrition status was 2.94% and nutrition insufficiency status was 1.47%. The test results obtained that p value = 0.032 means <0.05 indicates that there is an influence of environmental sanitation on the nutritional status of toddlers, good nutritional status of toddlers as much as 63.23%, while mothers with low levels of knowledge will have a poor nutritional status of 2.94% and underweight nutritional status of toddlers 2.94. Test results p value = 0.022 means <0.05 which indicates there is an influence of mother's knowledge on the nutritional status of toddlers. The influence of the family's economic level on the nutritional status of toddlers shows that a medium and high family economy has a good nutritional status on toddlers by 47.05% and 38.24%. While a low family economy will have 2.94 poor nutritional status and 4.42% poor nutritional status in toddlers. Test results p value = 0,000 means <0.05 which indicates that there is an influence on the level of the family's economy on the nutritional status oftoddlers. Based on the results of the study it can be concluded that there is an influence of environmental sanitation, the influence of mother's knowledge and family economy on the nutritional status of toddler in Lubuk Sakat Village, Kampar Regency. Therefore it is suggested to the relevant agencies to conduct counseling related to environmental sanitation, adding insight into mothers of toddlers about nutrition.